Toxic epidermal necrolysis in hepatitis A infection with acute-on-chronic liver failure: Case report and literature review - Zang, Xin; Chen, Si; Zhang, Lin; Zhai, Yongzhen (Frontiers in Medicine, 2022)
Toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS) are acute inflammatory skin adverse reactions characterized by epidermal exfoliation and multi-site mucositis and are considered medical emergencies. The risk factors for SJS/TEN include immune disorders, malignancy, and genetic susceptibility. In most cases, medication is considered to be the leading cause of TEN. In addition, several studies suggest that infections, such as the herpes simplex virus, human immunodeficiency virus (HIV), Mycoplasma pneumoniae, streptococcus, and meningococcus infections, can trigger the occurrence of SJS/TEN. In this rare case, we share our experience managing TEN in a hepatitis A virus infection with an acute-on-chronic liver failure patient. A 38-year-old man was infected with hepatitis A virus on the basis of liver cirrhosis and progressed to acute-on-chronic liver failure. As the infection progressed, the target-like skin lesions accompanied by mucosal involvement worsened. The condition of the patient progressively worsened with a severe generalized rash, bullae, and epidermal detachment accompanied by severe erosive mucosal lesions. His skin detachment area gradually involved 30% of the body surface area (BSA), and the disease progressed to TEN. The intravenous infusion of corticosteroids alleviated the patient's hypersensitivity, and the patient obtained lasting remission without severe adverse reactions and complications.